Harming the Beneficiaries of Humanitarian Intervention - Eggert, Linda (Ethical theory and moral practice, 2018)
This paper challenges one line of argument which has been advanced to justify imposing risks of collateral harm on prospective beneficiaries of armed humanitarian interventions. This argument - the 'Beneficiary Principle' (BP) - holds that non-liable individuals' immunity to being harmed as a side effect of just armed humanitarian interventions may be diminished by their prospects of benefiting from the intervention. Against this, I defend the view that beneficiary status does not morally distinguish beneficiaries from other non-liable individuals in such a way as to permit exposing them to greater risks of being harmed. The argument proceeds in four steps. I first show that the BP can neither be grounded in liability-based nor in lesser-evil justifications for harming. I then argue that a standalone justification for unintended harming based on beneficiary status would face at least two critical challenges. The first concerns the BP's applicability to collectives; the second questions the normative weight we can plausibly ascribe to beneficiary status when beneficiaries are such by virtue of being victims of wrongful threats of harm. I argue that standing to benefit is morally irrelevant when the benefit consists in the mitigation or prevention of wrongful harms, and consequently suggest that the BP may only serve as a distributive principle in allocating risks of harm if it is disambiguated in a number of critical aspects and applied in a more narrowlydefined set of circumstances.